Ryzyko w działalności międzynarodowej polskich przedsiębiorstw - Krokosz-Krynke, Zofia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
International activity of Polish enterprises grew up after Poland became a member state of the European Union. Import/export is considered to be a basic international activity. This type of activity is always accompanied by risk. A research done among Polish enterprises shows that import/export risk is noticed by small as well as by big companies. It appeared that goods risk is recognized as the most important one while country risk has the lowest meaning for Polish firms. The most popular method used to manage trade risk is collecting and analysing informations (details) about the client. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 252-264